Building Environmental Awareness Through Animation: Transforming Nature from Plastic Waste - Yasa, Gede Pasek Putra Adnyana; Wibawa, Arya Pageh; Pramayasa, I Made Hendra Mahajaya (Sean Institute, 2024)
This study examines the role of animation as an effective medium in socializing environmental issues, especially regarding plastic waste management. Through a qualitative approach, this study explores how animation can convey important messages related to reducing plastic waste and preserving the environment to various groups in society. In this case study, animation is used as a communication tool that emphasizes the importance of pro-environmental behavior through an attractive and easy-to-understand visual narrative. The results of the study indicate that animation has great potential to raise awareness and change people's behavior in dealing with plastic waste. With a combination of strong visuals and deep moral messages, animation has proven effective in healing nature from the negative impacts of plastic waste. These findings indicate the need for further development in the use of creative media, such as animation, as an innovative socialization strategy in environmental conservation efforts.